#### Answer

$\frac{IR}{E-Ir}=n$

#### Work Step by Step

$I=\frac{nE}{R+nr}$ ; n
We are trying to solve for the variable n. We must first multiply both sides by $(R+nr)$. We are doing this to cancel out the fraction.
$I\times(R+nr)=\frac{nE}{R+nr}\times(R+nr)$
$IR+Inr=nE$
We now subtract Inr from both sides.
$IR+Inr-(Inr)=nE-(Inr)$
$IR=nE-Inr$
From here we factor out n.
$IR=n(E-Ir)$
Lastly, you divide both sides by $ (E-Ir)$.
$\frac{IR}{E-Ir}=n\frac{E-Ir}{E-Ir}$
The fraction will cancel itself out, giving us our answer.
$\frac{IR}{E-Ir}=n$